Prevalence and Associated Factors with Ideal Cardiovascular Health Metrics in Bangladesh: Analysis of the Nationally Representative STEPS 2018 Survey - Rajat Das Gupta; Rownak Jahan Tamanna; Mohammad Rashidul Hashan; Maxwell Akonde; Shams Shabab Haider; Promit Ananyo Chakraborty; Md. Belal Hossain (MDPI AG, 2022)
This study aims to find out the prevalence of the American Heart Association's (AHA)'s cardiovascular health metrics and associated socio-demographic factors. A secondary analysis of the World Health Organization (WHO) STEPwise approach to surveillance survey 2018 (STEPS 2018) data was conducted. Ideal Cardiovascular Health (ICH) was defined as the presence of 5-7 ideal metrics as defined by the AHA. Design-adjusted multivariable logistic regression was used to determine the associated factors of ICH. In total, 5930 respondents were included in our analysis, and 43.1% of the participants had ICH. The odds of ICH decreased with age [compared to 18-29 years old individuals, 30-49 years: AOR (Adjusted Odds Ratio): 0.4; 95% Confidence Interval (CI): 0.4-0.5; 50-69 years: AOR: 0.7; 95% CI: 0.6-0.8], and higher educational attainment (compared to those who received no formal education, being educated up to primary level: AOR:0.7; 95% CI: 0.6-0.8; being educated up to secondary level: AOR: 0.4; 95% CI: 0.4-0.5; being educated up to college and higher: AOR: 0.4; 95% CI: 0.3-0.5). Compared with female and urban residents, the odds were 30% and 40% less among male and rural residents, respectively. The public health promotion programs of Bangladesh should raise awareness among high-risk groups to prevent cardiovascular diseases.